992 Nebulised Iloprost and Noninvasive Respiratory Support as a First Treatment for Hypoxaemic Respiratory Failure in Ex-Preterm Infants: Preliminary Experience. (October 2012) - Piastra, M; Luca, D de; Pietrini, D; Luca, E; Marzano, L; Rosa, G de; Visconti, F; Caliandro, F; Conti, G
Abstract : Objective: To describe a series of ex-preterm infants admitted to pediatric intensive care unit because of acute hypoxaemic respiratory failure complicated by pulmonary hypertension who were treated electively combining noninvasive ventilation (NIV) and nebulized iloprost (nebILO). Methods: Open uncontrolled observational study, Pediatric Intensive Care Unit, University Hospital. Measurements and Main Results: Ten formerly preterm infants with acute hypoxaemic respiratory failure and pulmonary hypertension, of whom 8 had moderate to severe bronchopulmonary dysplasia. Median age and body weight were 6.0 (2.75–9.50) months and 4.85 (3.32–7.07) kg, respectively. We observed a significant early oxygenation improvement in terms of PaO2 /FiO2 increase ( p =0.001) and respiratory rate reduction ( p =0.01). Hemodynamic also improved, as shown by heart rate (p=0.002) and pulmonary arterial pressure systolic/systolic systemic pressure (PAPs/SSP) ratio reduction (p=0.0137). NebILO was successfully weaned in positive response cases: 4 infants were discharged on oral sildenafil. Three patients failed noninvasive modality and needed invasive mechanical ventilation; hypoxic-hypercarbic patients were most likely to fail noninvasive approach. Only one patient requiring invasive ventilation died and surviving babies had a satisfactory 1-month post-discharge follow-up. Conclusions: The noninvasive approach combining NIV and nebILO for ex-preterm babies with respiratory failure and pulmonary hypertension resulted to be feasible and quickly achieved significant oxygenation and hemodynamic improvements.